A2.7 Concomitant transverse myelitis and guillain-barre syndrome after adalimumab therapy in a case with ankylosing spondylitis. (31st January 2014) - Ugurlu, Serdal; Saygin, Caner; Uzunaslan, Didem; Tascilar, Koray; Ince, Birsen; Saip, Sabahattin
Abstract : Background: The introduction of TNF inhibitors into clinical practice has revolutionalised the treatment of most inflammatory diseases. However, these drugs are associated with various and potentially serious side effects. Despite being rare, demyelinating neuroinflammatory disordes including multiple sclerosis, optic neuritis, transverse myelitis, polyradiculoneuropathy, and Guillain-Barre Syndrome (GBS) have been reported after using anti-TNF drugs, particularly with infliximab. Adalimumab is a newer fully humanised monoclonal anti-TNF antibody and to date, transverse myelitis during the course of adalimumab treatment has never been reported. Herein, we describe a patient who received adalimumab for management of his ankylosing spondylitis (AS) and developed synchronous transverse myelitis and GBS after therapy. Case Report: A 69-year old male with a 30-year history of AS, was admitted to neurology clinic with lower extremity weakness. Physical examination revealed bilateral 5/5 and 0/5 motor strengths in upper and lower extremities, respectively. He did not have sphincteric or sensorial deficits, cerebellar symptoms, or aphasia. He had received adalimumab treatment for 8 months (40 mg subcutaneously every 2 weeks) which controlled his refractory AS symptoms, but the patient had stopped taking the drug 3 months before the onset of his symptoms. MRI showed increased signal intensity at distal spinal cord which supported the diagnosis of myelitis. After one week course of pulse steroids, the patient responded well and gained full strength. One month later, he presented again with bilateral lower extremity weakness and falls, and physical examination showed full strength in upper extremity and muscle strength was 2/5 on right and 0/5 on left lower extremity. He had hypotonia and hyporeflexia on the right and areflexia on the left lower extremity. Repeated MRI scan showed regressed spinal lesion, lumbar puncture revealed elevated protein levels (107 mg/dL) and EMG was compatible with GBS. The patient received intravenous immunoglobulin and showed gradual improvement in lower extremity muscle strength. Conclusion: Central and peripheral progressive demyelinating neuroinflammatory lesions might occur during anti-TNF treatment, with the latter being more common than central nervous system involvement. There are a few reports indicating an association between adalimumab and GBS in patients with rheumatoid arthritis, but synchronous occurence of transverse myelitis and GBS is so unusual, and both diseases responded well to standard measures.